Evaluating damage in optical elements using an amplified spontaneous emission beam. (2nd December 2015) - Zhou, Qiong; Wang, Jiangfeng; Guo, Yajing; Liu, Dean; Zhu, Jianqiang
Abstract : A method to evaluate damage in optical elements with the near field of an amplified spontaneous emission (ASE) beam has been developed. Local peak intensities are generally distributed randomly in the near field of a laser beam. The partial coherence of the ASE source results in a very smooth beam profile. The coherence time of ASE is much less than the pulse width. Small-scale intensity modulations can be smoothed out rapidly within the time of a pulse width. In the experiments, ASE is generated from a multifunctional high-performance Nd:glass system, with a pulse duration of 3 ns, a spectral width (full width at half maximum, FWHM) of 1 nm and an adjustable energy range from 1 to 10 J. The damage thresholds of samples induced by ASE are two to three times higher than those induced by a laser with the same size of test spot. Furthermore, the ASE beam has great potential for the detection of defects over a large area and the conditioning of optical elements.